Enhanced Short-Time Thermal Transient Model and Testing Procedure for High Power Density Motors, Such as in Supercar Traction - Paolo Pescetto; Gaetano Dilevrano; Fausto Stella; Gianmario Pellegrino; Aldo Boglietti (IEEE Open Journal of Industry Applications, 2025)
The short-time thermal transient (STTT) test is an efficient and precise method for determining the winding thermal capacitance and winding-to-back-iron thermal resistance in ac motors. Traditionally validated for industrial motors, the STTT procedure involves a brief dc excitation with motor phases connected in series, followed by analysis using a first-order lumped parameter thermal network. However, for traction motor drives where phase terminals may be inaccessible, the standard all-in-series STTT procedure is not feasible. Moreover, in such highly loaded traction motors, the estimated thermal parameters are sensitive to dc excitation duration, making the first-order STTT model unsuitable. This article presents an STTT model of higher order along with an optimized testing sequence and data processing approach, extending the applicability of this method to traction and high-power-density motors. Experimental validation on two commercial supercar traction motors demonstrates the effectiveness of the proposed model and procedure, to be considered an upgrade of wider and more general validity of the existing first-order STTT method.